Haemolytic uraemic syndrome associated with pancreatitis: report of four cases and review of the literature - Sandino-Pérez, Justo (Clin Kidney J, 2021)
BACKGROUND: The incidence of acute kidney injury (AKI) in patients with acute pancreatitis ranges from 15% to 40% and is associated with poor prognosis. Haemolytic uraemic syndrome (HUS) in the setting of acute pancreatitis is an uncommon association with fewer than 30 cases reported in the literature. METHODS: A retrospective review of the clinical records at our institution between January 1981 and December 2019 was carried out to identify patients with acute pancreatitis and HUS. Additionally, a literature review was conducted on this topic. The aims of the study were to describe the clinical course and outcomes of patients affected by this condition. RESULTS: Four cases of HUS following an acute pancreatitis were identified. The mean (±SD) age of the study group was 30 ± 6 years, all of which were males. Excessive alcohol consumption was the main cause of acute pancreatitis in all four patients. HUS with progressive AKI developed in a median interval of 2 days from the onset of pancreatitis (range 1–3 days). All patients required kidney replacement therapy during the course of follow-up. A kidney biopsy was performed in two patients, showing typical thrombotic microangiopathic features. One case was treated with eculizumab, whereas the rest were treated with supportive care and/or plasma exchange. A normalization of haematological parameters and complete recovery of kidney function were observed in all patients at last follow-up, although this improvement was significantly faster in the patient treated with eculizumab. CONCLUSIONS: HUS may infrequently develop in patients with acute pancreatitis. An early identification of this complication is mandatory, and complement blockade with eculizumab may be associated with a faster kidney function recovery.